Experimental Study and numerical Simulation on Air-water Tube Fin Heat Exchanger - 何明勋; 陶正良; 王冬梅 (Zhileng xuebao)
To get the tube fin heat exchanger's performance curve relationship,a series of experimental studies and numerical simulations were cautiously carried out. At the same time,as another part of the 3-D numerical simulation work,this tube fin heat exchanger's internal temperature,velocity and pressure fields were shown in this paper. From the results of experimental study and numerical simulation,we found that the real tube fin heat exchanger's transfer factor j is 12% lower than that of the simulation model,while the friction factor j is 4%-16% increased. Fin spacing and density of the staggered tube bundle have much more influence on its performance,when the distance between fins decreased or the tube distributing density increased,heat transfer of the exchanger will be strengthened and pressure drop will be distinctly aggrandized.